Evaluation of Plantaricin Gene Expression in Lactiplantibacillus plantarum Strain SU-KC1a: [Evaluasi Ekspresi Gen Plantarisin pada Lactiplantibacillus plantarum Strain SU-KC1a] - Sugata, Marcelia; Sunardi, Jessica; Victor, Hans; Tan, Tjie Jan (FaST - Jurnal Sains dan Teknologi (Journal of Science and Technology), 2025)
Lactobacillus species are normal gastrointestinal flora and are commonly used in the food industry for fermented milk products. Due to their probiotic properties, Lactobacillus strains are considered safe and effective for human consumption, with antimicrobial activity often attributed to bacteriocins. Lactobacillus plantarum (known as Lactiplantibacillus plantarum) produces plantaricin, a ribosomally synthesized bacteriocin with activity against a range of pathogens and potential as a bio-preservative. In this study, L. plantarum SU-KC1a, isolated from human breast milk, was assessed for its antimicrobial activity through the production of plantaricin. Since plantaricin is typically produced at low concentrations, reverse transcription polymerase chain reaction (RT-PCR) was employed. PCR amplification of the plnJ and plnK genes resulted in amplicons of approximately 168 bp and 173 bp, respectively. These findings suggest that L. plantarum SU-KC1a produces plantaricin JK. However, further sequence analysis is required to confirm the homology of the amplified genes with known plantaricin J and K genes in GenBank. Bahasa Indonesia Abstract: Spesies Lactobacillus adalah flora gastrointestinal normal dan sering digunakan dalam industri makanan untuk produk susu fermentasi. Karena sifat probiotiknya, strain Lactobacillus dianggap aman dan efektif untuk konsumsi manusia, dengan aktivitas antimikroba yang sering dikaitkan dengan bakteriosin. Lactobacillus plantarum (dikenal sebagai Lactiplantibacillus plantarum) menghasilkan plantarisin, sebuah bakteriosin yang disintesis ribosom dengan aktivitas melawan berbagai patogen dan berpotensi sebagai bio-preservatif. Dalam penelitian ini, L. plantarum SU-KC1a yang diisolasi dari ASI manusia dievaluasi aktivitas antimikrobanya melalui produksi plantarisin. Karena plantarisin biasanya diproduksi dalam konsentrasi rendah, dilakukan reverse transcription polymerase chain reaction (RT-PCR). Amplifikasi PCR dari gen plnJ dan plnK menghasilkan produk amplifikasi sekitar masing-masing 168 bp dan 173 bp. Hasil tersebut mengindikasikan bahwa L. plantarum SU-KC1a menghasilkan plantarisin JK. Namun, analisis urutan lebih lanjut diperlukan untuk mengonfirmasi kesamaan gen yang diamplifikasi dengan gen plantarisin J dan K yang diketahui di GenBank.